Kuat Tekan Beton Geopolimer Menggunakan Fly Ash Sebagai Pengganti Semen dengan Bahan Tambah NaOH dan Na2SiO3 - Sari, Novita; Jannah, Nurlina; Flaviana Tilik, Lina; Syahira, Nurul Aina (PILAR, 2025)
Geopolymer concrete is an environmentally friendly alternative because it does not use cement, thus reducing carbon emissions and utilizing industrial waste. In this study, three variations of geopolymer concrete mixtures were prepared with activator solution to fly ash ratios: BG 3:1, BG 4:1, and BG 5:1, as well as one variation of normal concrete as a comparison. Compressive strength tests were conducted at 7, 14, and 28 days, using a curing method using a plastic cover to maintain moisture during the hardening process. The test results showed that the higher the activator solution ratio, the higher the resulting compressive strength. The 5:1 BG variation yielded the best results, reaching a compressive strength of 414.8 kg/cm² at 28 days, exceeding that of conventional concrete, which only reached 255.6 kg/cm². Meanwhile, the 3:1 BG variation yielded the lowest results and did not meet the K-225 concrete quality target. This study concludes that geopolymer concrete has the potential to be used as an alternative to conventional concrete, provided the material composition and activator solution ratio are properly adjusted. The use of fly ash also offers a solution for recycling industrial waste.